Production of Vowel /ə/ in Sundanese by Japanese Native Speakers in First Exposure - Rike Febriyanti; Lailatul Husna (Lingua Cultura, 2020)
The research described native Japanese speakers’ perception of Sundanese vowel /ə/ after the first exposure to a controlled naturalistic input of conversation. The research worked in respect of Brown’s model of L2 speech perception and L1 feature geometry, which sought to relate theories of segmental phonology to L2 speech perception and the first exposure treatment. Some Sundanese native speakers conducted a conversation that contained the /ə/ vowel in front of five Japanese native speakers with no prior exposure to Sundanese. Therefore, the researchers had collected speech data from five L1 Japanese native speakers (three males, two females, Mage = 22, SD = 2,1). The Japanese were asked to listen to the short conversation and imitate vowel /ə/, which did not exist in the Japanese language vowel inventory. The observation confirmed Brown’s hypothesis that L2 perception of /ə/ vowel was constrained by the L1 feature geometry. L1 Japanese language phonological properties worked as a perceptual filter to Sundanese L2 input, causing the Japanese L2 learners to perceive only the vowel discriminated by phonological features presented in Sundanese. The data show that the Japanese native speakers are able to overcome the perceptual filters so they can produce various frequencies of vowel /ə/, which are statistically similar to the frequency produced by Sundanese native speakers. The research implies that the possibility of learning new sounds from an entirely new language is wide open when the learner is able to pass through the L1 perceptual filter.